DAMPAK FUNDAMENTAL TERHADAP HARGA SAHAM PERBANKAN GO PUBLIC DI BURSA EFEK INDONESIA PERIODE 2020 - 2021 - Gusti Ayu Imas Adi Ningsih; Komang Agus Rudi Indra Laksmana; I Nyoman Gede Supraptha (Nusantara Hasana Berdikari, 2022)
This study aims to determine the effect of Net Interest Margin (NIM), and Loan To Deposit Ratio (LDR) on stock prices of banking companies listed on the Indonesia Stock Exchange (IDX) in 2020 – 2021. The population in this study are four capitalist banking companies. Biggest market. The sample of this study were 4 banks, namely BCA, BRI, BNI and MANDIRI which met the criteria. The data collection methods were in the form of documentation techniques and multiple linear regression analysis as analytical techniques. The results of this study indicate that the Net Interest Margin and Loan To Deposit Ratio simultaneously have a significant effect on stock prices. Based on the partial test results Net Interest Margin has a positive effect on stock prices, Loan To Deposit Ratio has a positive effect on stock prices, Suggestions that can be given are that further research is expected to add other independent variables that can measure the soundness of the bank which will also affect the return share.